Genetic architecture underlying variation in floral meristem termination in Aquilegia. (22nd June 2022) - Min, Ya; Ballerini, Evangeline S; Edwards, Molly B; Hodges, Scott A; Kramer, Elena M
Abstract : Using the natural variation in stamen whorl numbers in Aquilegia species, we conducted QTL mapping to uncover the genetic architecture underlying variation in floral meristem termination. Abstract: Floral organs are produced by floral meristems (FMs), which harbor stem cells in their centers. Since each flower only has a finite number of organs, the stem cell activity of an FM will always terminate at a specific time point, a process termed floral meristem termination (FMT). Variation in the timing of FMT can give rise to floral morphological diversity, but how this process is fine-tuned at a developmental and evolutionary level is poorly understood. Flowers from the genus Aquilegia share identical floral organ arrangement except for stamen whorl number (SWN), making Aquilegia a well-suited system for investigation of this process: differences in SWN between species represent differences in the timing of FMT. By crossing A. canadensis and A. brevistyla, quantitative trait locus (QTL) mapping has revealed a complex genetic architecture with seven QTL. We explored potential candidate genes under each QTL and characterized novel expression patterns of select loci of interest using in situ hybridization. To our knowledge, this is the first attempt to dissect the genetic basis of how natural variation in the timing of FMT is regulated, and our results provide insight into how floral morphological diversity can be generated at the meristematic level.